2019
DOI: 10.3389/fneur.2019.00840
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Telemedicine to Improve Pediatric Concussion Care in Rural and Remote Communities in Canada

Abstract: Concussion is a form of mild traumatic brain injury that affects thousands of Canadian children and adolescents annually. Despite national efforts to harmonize the recognition and management of pediatric concussion in Canada, timely access to primary and specialized care following this injury remains a challenge for many patients especially those who live in rural and remote communities. To address similar challenges facing patients with stroke and other neurological disorders, physicians have begun to leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 74 publications
(86 reference statements)
2
37
0
Order By: Relevance
“…A research performed on 210 subjects showed, as expected, that people use search engines to learn about serious or highly stigmatic conditions, but surprisingly, an important amount of sensitive health information is sought and shared via social media [69]. The term telemedicine meaning "healing at a distance" was introduced in 1970 [70].…”
Section: Worldwide Tendencies: Community Health Worker (Chw) Misinformation and Telemedicine In Home-based Care For Childrenmentioning
confidence: 90%
“…A research performed on 210 subjects showed, as expected, that people use search engines to learn about serious or highly stigmatic conditions, but surprisingly, an important amount of sensitive health information is sought and shared via social media [69]. The term telemedicine meaning "healing at a distance" was introduced in 1970 [70].…”
Section: Worldwide Tendencies: Community Health Worker (Chw) Misinformation and Telemedicine In Home-based Care For Childrenmentioning
confidence: 90%
“…In a second manuscript identified in our scoping review, Ellis and Russell (2019) concluded that, similar to models of care established for acute stroke, provincial paediatric concussion programs and clinics can use telemedicine to partner with smaller regional hospitals and community healthcare centres to establish hub-and-spoke type networks that improve access to specialised primary and multi-disciplinary care for patients living in rural and remote regions of Canada [ 14 ].…”
Section: Preliminary Experience Of the Pan Am Clinic Connect Programmentioning
confidence: 99%
“…More recently, preliminary research has demonstrated that telemedicine can provide timely access to safe and cost-effective paediatric concussion care within medically underserved communities [13]. Similar to established systems of care for acute stroke, additional work suggests that telemedicine-based networks may provide an innovative approach that connects paediatric concussion patients living in rural, remote and isolated communities to regional multi-disciplinary concussion programmes located in distant urban settings [14]. Although clinical care of paediatric concussion in Canada is directed by up-to-date and harmonised national evidence-based clinical guidelines [15,16], none provide guidance on the appropriate use of telemedicine.…”
mentioning
confidence: 99%
“…While the CCM has used telehealth for some established, follow-up patient visits, it has not been, prior to 2020, routinely and widely integrated into practice, although using this type of service has shown some benefits in the concussion population. 26 Now, as stated above, with the current pandemic climate and need for social distancing, services like telehealth for outpatient visits are more in favor than in-person visits or canceling visits. 27 Other concussion-related testing and services are available via handheld devices which can aid in providing objective measurements to gauge concussion recovery.…”
Section: Future Directionsmentioning
confidence: 99%